Estimasi Stok Karbon Pada Biomassa Mangrove Dusun Poton Bako, Lombok Timur - Ramadhan, Moch Fitrah; Paryono; Rahman, Ibadur (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2025)
Global warming occurs as a result of greenhouse gas emissions and has become one of the world's biggest environmental problems today. Mangrove ecosystems play an important role in mitigating global warming through their ability to absorb and store carbon in their biomass. This study aims to determine the vegetation composition, biomass, and estimated carbon stock in mangrove biomass in the Poton Bako Hamlet mangrove area, Jerowaru District, East Lombok. The method used is a non-destructive method by measuring trunk diameter (DBH) using an allometric model approach to calculate above-ground and below-ground biomass, which is then converted into carbon stock. Four mangrove species were found at the research location: Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, and Sonneratia alba. The mangrove density in Poton Bako Hamlet is 2,611.11 individuals/ha, categorized as dense. Sonneratia alba is the mangrove species with the highest biomass content among the other species, with above-ground biomass values of 61.37 tons/ha and below-ground biomass of 33.04 tons/ha, with a total carbon stock value of 43.43 tonsC/ha. The total above-ground biomass value of the Poton Bako mangroves is 110.22 individuals/ha, and the below-ground biomass is 52.16 tons/ha. With this biomass value, the Poton Bako mangrove area is estimated to have a total carbon stock of 74.69 tonsC/ha, consisting of 50.70 tonsC/ha above-ground carbon stock and 23.99 tonsC/ha below-ground carbon stock.